Exploring the communicative function of light, sound and colour in Hotel Rwanda - Rwafa, Urther; Vambe, Maurice (Intellect, 2016)
This article explores the communicative function of light, colour and sound, as constitutive elements of the construction of the narrative of genocide in Hotel Rwanda. Such an exploration is deliberately performed against the tendency to approach the film in ways that only emphasize the importance of ethnicity and class factors. The assumption of this article is that in film, light, colour, visuals, and sound are not external accessories but simultaneously function as the meaning, content, and form of the film. An exploration of the intersections and the uses to which light, sound, colour and visuals are put in the film can also reveal the range of a director’s power to manipulate these in ways that can fortunately bring into view some narratives of the Rwandan genocide that could have been hidden from view by an overemphasis on the analysis of verbal language only, during interpretation of the film.